A new benzyl ester and ergosterol derivatives from the fungus Gymnoascus reessii - Kitchawalit, Sasiwimon; Kanokmedhakul, Kwanjai; Kanokmedhakul, Somdej; Soytong, Kasem (My University, 2014)
A new benzyl ester, reessiate (1), anthraquinone, islandicin (2), ergosterol and seven ergosterol derivatives (3-9) were isolated from the fungus Gymnoascus reessii. All structures were identified by spectroscopic methods. This is the first report of their isolation from this fungus. Compounds 4-7 and 9 exhibited antimalarial activity against Plasmodium falciparum with IC 50 values in the range of 3.3-4.5 μg/mL. In addition, 4 showed cytotoxicity against KB, MCF7 and NCI-H187 cancer cell lines. It was found that 4 has cytotoxic effect to MCF7 (IC50 = 7.9 μg/mL) lower than Doxorubicin (IC50 = 8.5 μg/mL). © 2014 Taylor & Francis.
Keywords: antimalaria; benzyl ester; cytotoxicity; ergosterol derivative; Gymnoascus reessii